UNVEILING THE ROLE OF CULTURAL DIVERSITY IN INDIAN MODERN POLITICS - Jakhar, Dr. Monika (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This study encompasses the full analysis of the widespread importance of cultural diversity in Indian contemporary politics. The intricate interplay between India's rich tapestry of cultures and its democratic political landscape is analyzed, highlighting the profound influence of diverse ethnicities, religions, and customs. From historical foundations to modern dynamics, the abstract digs into how cultural variety impacts policies, governance systems, and the democratic spirit itself. The representation of various groups in decision-making processes, the ideological landscape of political parties, and the federal structure of the political system are considered as major features of this effect. The abstract also touches upon the challenges and opportunities posed by cultural diversity, acknowledging its role in social movements and political activism. Ultimately, it underscores how India's commitment to democracy is inseparable from its celebration and recognition of cultural differences, emphasizing that the integration of diversity into the political discourse is a source of strength that defines the nation in the 21st century.